Evaluation of the Urine Dipstick Analysis for Detection of Bacteriuria - Wannasilp, Nilrat; Gonggetyai, Vangnarm; Viriyataveekul, Ronnachai; Komolpis, Podjanee (Siriraj Medical Journal, 2020)
This retrospective study was performed to evaluate the urine dipstick (leukocyte esterase and nitrite test) for detection of bacteriuria and pyuria. Of the 1,000 specimens, 296 (29.6%) had positive culture results. The dipstick (either leukocyte esterase or nitrite test) test for detection of bacteriuria had a sensitivity of 85%, specificity of 51%, positive predictive value of 42% and negative predictive value of 89%, and the leukocyte esterase test for the detection of pyuria had a sensitivity of 96%, specificity of 73%, positive predictive value of 75% and negative predictive value of 95%. The sensitivity and negative predictive value of the dipstick test in the pediatric group was the lowest values when compared with the other groups. We conclude that, 1) The dipstick test may be used as a screening test for pyuria 2) This test could not be used as a screening test for urinary tract infection (UTI) 3) In contrast to sex, age affect the results of the urine dipstick test 4) This test has good result in adult particularly old age but, not in children.